Effects Of Immune Cells On Mesenchymal Stem Cells During Fracture Healing - Ehnert, Sabrina; Relja, Borna; Schmidt-Bleek, Katharina; Fischer, Verena; Ignatius, Anita; Linnemann, Caren; Rinderknecht, Helen; Huber-Lang, Markus; Kalbitz, Miriam; Histing, Tina; Nussler, Andreas K. (World Journal of Stem Cells, 2021)
In vertebrates, bone is considered an osteoimmune system which encompasses functions of a locomotive organ, a mineral reservoir, a hormonal organ, a stem cell pool and a cradle for immune cells. This osteoimmune system is based on cooperatively acting bone and immune cells, cohabitating within the bone marrow. They are highly interdependent, a fact that is confounded by shared progenitors, mediators, and signaling pathways. Successful fracture healing requires the participation of all the precursors, immune and bone cells found in the osteoimmune system. Recent evidence demonstrated that changes of the immune cell composition and function may negatively influence bone healing. In this review, first the interplay between different immune cell types and osteoprogenitor cells will be elaborated more closely. The separate paragraphs focus on the specific cell types, starting with the cells of the innate immune response followed by cells of the adaptive immune response, and the complement system as mediator between them. Finally, a brief overview on the challenges of preclinical testing of immunebased therapeutic strategies to support fracture healing will be given
CRIS-Team Scopus Importer:2021-12-24
Keywords: Bones; Fracture healing; Immune response; Mesenchymal stem cells; Trauma